Nutrition Literacy as a promoter of Critical Environmental Education in Elementary Education: a necessary articulation - Fornazari, Valéria Brumato Regina; Obara, Ana Tiyomi (Electronic Journal "Fórum Ambiental da Alta Paulista", 2023)
It is unquestionable that Food and Human Nutrition, as school contents, are extremely important, since they aim to promote human and citizen development, while making students capable of managing and choosing the foods they will consume, from a critical reflection, in order to directly and decisively impact the health and longevity of students. However, this theme cannot be restricted to discussing only issues related to food, as the formation and perpetuation of healthy eating habits depends on the holistic understanding of the eating process. Thus, this work aimed to develop Pedagogical Workshops, with elementary school II students, from a public school, to articulate reflections on Literacy in Human Nutrition and Critical Environmental Education based on the theme: “How can my power of food choice impact on the society?". Through this pedagogical intervention, it was possible to verify that students have a hygienist view of human food, perceiving it as an isolated act, which impacts exclusively on their own health, evidencing the need and urgency of articulation between Critical Environmental Education and Literacy Nutrition in Basic Education.
Keywords: Human Nutrition.; Scientific Literacy; Citizenship